Tren Penelitian Arsitektur Nusantara: Sebuah Tinjauan Literatur dengan Pendekatan Analisis Bibliometrik - Muhammar Khamdevi (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2023)
The discourse on "nusantara" architecture has been echoing since 1999. The topic of this research tried to separate itself from ethnographic studies, vernacular architecture, and traditional architecture. This research wanted to build studies on local architectural understanding theoretically to its current application practices and projections of its existence in the future. This study aimed to analyze the trend in "nusantara" architecture research objectively that has been rolling for 24 years by using a bibliometric analysis method using big data provided by Lens, then visualized them using Lens analysis data, Microsoft Excel 35 version 2212 software, and VOSviewer software. This study's results indicated that the research topics on "nusantara" Architecture are not many and varied and have not formed many publication networks.